White In. White Out. The Noticeability of Text. Conspicuous Text - Frost, Sabine (Nordlit, 2008)
The term ‘whiteout' is usually understood as a weather condition in polar or mountain regions affecting visibility through diffuse lighting. In this case, however, the idea of ‘whiteout' is not merely taken as a motif, but as a way to describe disruptive effects in literary texts. The term ‘whiteout' is used here to point out how ‘snow'-in the broadest sense-pervades the structure and language of narrative texts from the 19th to the 21st century. The texts in question deal with snowstorms and snow drifts; they send their protagonists on polar explorations and mountain expeditions; heros get lost in snow or suffer from extreme frost.